Meningkatkan Prestasi Belajar Matematika Menggunakan Model Kooperatif Tipe Jigsaw pada Peserta Didik SMK Negeri 1 Sakra - Sulhiah Sulhiah (AS-SABIQUN, 2019)
Cooperative learning methods of learning are not just working together, but rather on structuring. So that cooperative learning is defined as structured group learning. The purpose of writing: (a) obtaining the influence of Jigsaw type cooperative models on Mathematics learning outcomes. (b) To find out the mastery of Mathematics after the implementation of Jigsaw cooperative learning. Classroom action research (action research) is carried out in three cycles. Each cycle consists of stages namely: design, observation, reflection, and revision. The focus of this writing is students of Class XI SMK 1 East Sakra Lombok. Data obtained in the form of formative test results, observation sheets of learning activities. So it was found that the learning ability of students has increased from cycle I to cycle III namely, cycle I (66.67%), cycle II (75.00%), cycle III (87.50%). The Jigsaw type cooperative model has a positive effect on the learning effect of Class XI Students of SMKN 1 Sakra East Lombok.